Economic reforms in India An overview - "Agrawal , Babita" (Jaipur, 2008)
The papers contributed by the eminent scholars in this book deals with the impact of economic reforms on various sectors of our economy. The authors have given valuable suggestions to bring improvement in our steps towards making our country comparable with other countries of the world
Keywords: Economic reforms